Leaf anatomy of Pandanus species (Pandanaceae) from Java - Rahayu, Sri Endarti; Kartawinata, Kuswata; Chikmawati, Tatiek; Hartana, Alex (REINWARDTIA, 2012)
The leaf epidermis and mesophyll of fifteen species of Pandanus from Java were investigated to assess the value of anatomical features in species identification and classification. Characters of diagnostic importance are epidermal cell shape, differentiation of the abaxial epidermis into costa and intercosta, adaxial anticlinal cell wall outline, occurrence of raphides in the mesophyll, distribution of cubical crystals, pallisade cell shape, papillae on epidermal cells, and the stomatal complex. Leaf epidermal anatomy was found to be useful in the identification at species level.